Efficacy of insect larval meal to replace fish meal in juvenile barramundi, Lates calcarifer reared in freshwater - Katya, Kumar; Borsra, M.Z.S.; Ganesan, Dev; Kuppusamy, Giva; Herriman, Max; Salter, Andrew; Ali, Sayed Azam (Springer, 2017)
The present experiment was conducted to evaluate the efficacy of dietary protein from black soldier fly, Hermetia illucens, larval meal (BSFL) to replace fish meal (FM) protein in juvenile barramundi, Lates calcarifer. Larvae of black soldier fly were fed with the underutilised crop, sesbania, Sesbania grandiflora. Five isonitrogenous (44% crude protein) and isocaloric (16.0 kJ available energy/g) experimental diets were formulated to replace FM using processed BSFL meal at 0 (control), 25% (BSFL25), 50% (BSFL50), 75% (BSFL75) and 100% (BSFL100). Data for proximate and amino acid analysis suggested BSFL meal as an inferior protein ingredient than FM, but parallel to soybean meal. At the end of 8 weeks of fish feeding trial, there were no significant differences in the average weight gain (WG) and specific growth rate among the group of fish-fed control, BSFL25 and BSFL50 diets (P < 0.05). Although numerical differences were recorded in the fish whole-body proximate composition, crude protein and moisture content were not much affected by the different dietary treatments. Essential amino acids including arginine, histidine, lysine and methionine were found to be higher in the whole body of fish-fed BSFL100 diet. Broken line regression analysis of average WG showed an optimum FM replacement level of 28.4% with BSFL meal. Therefore, the present experiment clearly demonstrates that the maximal dietary inclusion level of BSFL meal as FM protein replacer for the optimum growth of juvenile barramundi reared in freshwater could be greater than 28.4% but less than 50%, without any adverse effects on the fish whole-body proximate and amino acid composition.